Trabecular Bone Score and Bone Quality in Systemic Lupus Erythematosus Patients - Barbara Ruaro; Andrea Casabella; Andrea Casabella; Sabrina Paolino; Sabrina Paolino; Elisa Alessandri; Massimo Patané; Emanuele Gotelli; Emanuele Gotelli; Alberto Sulli; Alberto Sulli; Maurizio Cutolo (Frontiers in Medicine, 2020)
Background: Systemic lupus erythematosus (SLE) patients run a higher risk of having low bone mass due to multifactorial events that include physical inactivity, persistent inflammation, low vitamin D levels, and glucocorticoid treatment. This study aimed at obtaining a comparison between bone involvement in SLE patients and healthy matched subjects (HS).Methods: A total of 40 SLE females (average age 54.1 ± 16.3 years) and 40 age–gender matched HS (average age 54.2 ± 15.9 years) were enrolled after having obtained informed written consent. Bone mineral density (BMD, g/cm2) of the lumbar spine (L1–L4) was analyzed by a dual-energy X-ray absorptiometry (DXA) scan (GE, Lunar Prodigy). The lumbar spine trabecular bone score (TBS) was derived for each spine DXA examination by the TBS index (TBS iNsight Medimaps).Results: The lumbar spine TBS score was statistically significantly lower in SLE patients than in HS (0.797 ± 0.825 vs. 1.398 ± 0.207, p < 0.001, as was BMD (p < 0.001) in all areas examined.Conclusions: SLE is associated with significant low bone mass as evidenced by DXA and TBS. This study emphasizes the importance of using DXA and TBS in the evaluation of the different aspects of bone architecture.